Conjugation of Polymer-Coated Gold Nanoparticles with Antibodies—Synthesis and Characterization - Gamze Tan; Karsten Kantner; Qian Zhang; Mahmoud G. Soliman; Pablo del Pino; Wolfgang J. Parak; Mehmet A. Onur; Daniel Valdeperez; Joanna Rejman; Beatriz Pelaz (Nanomaterials, 2015)
The synthesis of polymer-coated gold nanoparticles with high colloidal stability is described, together with appropriate characterization techniques concerning the colloidal properties of the nanoparticles. Antibodies against vascular endothelial growth factor (VEGF) are conjugated to the surface of the nanoparticles. Antibody attachment is probed by different techniques, giving a guideline about the characterization of such conjugates. The effect of the nanoparticles on human adenocarcinoma alveolar basal epithelial cells (A549) and human umbilical vein endothelial cells (HUVECs) is probed in terms of internalization and viability assays.